Analysis of turbulent flow and heat transfer over a double forward facing step with obstacles - Öztop, Hakan Fehmi; Mushatet, Khudheyer S.; Yilmaz, Ilker (Pergamon-Elsevier Science Ltd, 2012)
A numerical study has been conducted to analyze the turbulent forced convection heat transfer for double forward facing step flow with obstacles. Obstacles have rectangular cross-sectional area with different aspect ratio that is located before each step. The numerical solutions of continuity, momentum and energy equations were solved by using a commercial code which uses finite volume techniques. The effect of turbulence was modeled by using a k-epsilon model. The effects of step height, obstacle aspect ratio and Reynolds number on the flow and heat transfer are investigated. The obtained results show that the rate of heat transfer is enhanced as aspect ratio of obstacle increases and this trend is affected by the step height. Also the results verified that the pressure drop decreases as obstacle aspect ratio increases. (c) 2012 Elsevier Ltd. All rights reserved.
Keywords: Double forward facing step; Duct flow; Turbulence; Obstacle